2023
DOI: 10.3390/vaccines11030638
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Booster Hesitancy in Malaysia: A Web-Based Cross-Sectional Study

Abstract: Vaccination is a key public health strategy that is known to be effective in mitigating the risk of infection and severe disease. However, in the context of the COVID-19 pandemic, the percentage (<50%) of Malaysians who have received a booster for the COVID-19 vaccine has remained stagnant over a year. This study aimed to determine the prevalence of and the factors associated with hesitancy toward the second dose of booster for the COVID-19 vaccine. A web-based cross-sectional study was conducted from Augus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The possible reason behind strong recommendations to family members could be the high number of cases when the survey was conducted. Similarly, a previous study has reported a higher number of cases and belief that vaccine reduces the risk of infection and opinions from friends and family members that booster is helpful to have a higher impact in increasing the acceptance of booster dose ( Lee et al, 2023 ). Similarly, in this study, 53.9% of participants believe the risk of getting sick with COVID-19 is bigger than the vaccine's side effects.…”
Section: Discussionmentioning
confidence: 79%
“…The possible reason behind strong recommendations to family members could be the high number of cases when the survey was conducted. Similarly, a previous study has reported a higher number of cases and belief that vaccine reduces the risk of infection and opinions from friends and family members that booster is helpful to have a higher impact in increasing the acceptance of booster dose ( Lee et al, 2023 ). Similarly, in this study, 53.9% of participants believe the risk of getting sick with COVID-19 is bigger than the vaccine's side effects.…”
Section: Discussionmentioning
confidence: 79%
“…Others have also found that vaccine hesitancy is more common among the Muslims due to concerns of safety, and the 'halal' status of the vaccines [25]. Nevertheless, augmenting clinical studies on COVID-19 booster doses, providing guidance from healthcare professionals or policymakers and addressing side effect concerns could bolster public confidence and vaccine uptake [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to concerns about the safety of the vaccine, there was a significant decline in the intention to vaccinate immediately [ 39 ]. Vaccine hesitancy was also reported but with lower frequency among the Malaysian population, as more than 20% of the participants in the study showed hesitancy to get the second booster of the COVID-19 vaccine [ 40 ].…”
Section: Discussionmentioning
confidence: 99%